The integrity of Joseph Chambers [videorecording (DVD)] - Crawford, Clayne, 1978-; Brewster, Jordana, 1980-; Raymond-James, Michael (Gravitas Ventures, 2023)
Desperate to acquire the skills necessary to provide for his family in case of an apocalypse, insurance salesman Joseph Chambers goes deer hunting for the first time ever, alone, when his experienced buddy is too sick to join him.